Burden of laryngeal cancer in China caused by smoking from 1990 to 2021 and predictions for 2035: An age-period-cohort analysis of global burden of disease study 2021 - Xue Gu; Xiaopeng Sun; Xiao Ren; Yu Li; Yingying Fang; Hui Song; Pingli Luo; Mengfan Yuan (Tobacco Induced Diseases)
Introduction Smoking is a major risk factor for laryngeal cancer (LC). Understanding the impact of smoking on the changing disease burden of LC is crucial for LC prevention in China and provides a scientific basis for formulating targeted LC prevention and control strategies, contributing to the achievement of the ‘Healthy China 2030’ goals.